2022
DOI: 10.3390/ijerph19148533
|View full text |Cite
|
Sign up to set email alerts
|

Carpooling Systems for Commuting among Teachers: An Expert Panel Analysis of Their Barriers and Incentives

Abstract: Sustainable mobility is a current challenge in our society. Research shows that carpooling systems are potential solutions that could mitigate environmental pollution and urban congestion and provide cost savings for their users. Despite their potential benefits, the levels of carpooling practices among some occupations could be improved. Teachers are suitable for carpooling experiences due to their specific working conditions (e.g., timetables, destinations changes, path matches); however, there is no researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Car‐pooling tax breaks could further incentivize critical skills workers (Rey‐Merchán et al, 2022). We call on governments to examine commute trip reduction programmes such as paid car share benefits for critical skills workers where the employer provides an allowance for car sharing taking into account location and employee requirements (shift patterns and working time arrangements).…”
Section: Potential Solutionsmentioning
confidence: 99%
“…Car‐pooling tax breaks could further incentivize critical skills workers (Rey‐Merchán et al, 2022). We call on governments to examine commute trip reduction programmes such as paid car share benefits for critical skills workers where the employer provides an allowance for car sharing taking into account location and employee requirements (shift patterns and working time arrangements).…”
Section: Potential Solutionsmentioning
confidence: 99%
“…A relevant aspect for users is travel planning. Due to their inflexible timetables, long-term planning is provided by the system [27]. Another important attribute is the high number of potential users.…”
Section: Requirements Of a Carpooling System For Teachersmentioning
confidence: 99%
“…Another important attribute of the model proposed is the free election of the carpoolers by the users [27]. An automatic election by the system could generate trips composed of workmates with low personal affinity.…”
Section: Requirements Of a Carpooling System For Teachersmentioning
confidence: 99%
See 1 more Smart Citation
“…Correia & Viegas ( 2011) have stated that carpooling system needs to gain trust among the users. Another study by Rey-Merchán et al (2022) identified that carpooling isn't feasible for a short distance. Ni et al (2016) stated that passengers' information should be secured in the carpooling system.…”
Section: Introductionmentioning
confidence: 99%